2020
DOI: 10.12688/f1000research.16315.1
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of intellectual disability: advancing technology and gene editing

Abstract: Intellectual disability (ID) is a neurodevelopmental condition affecting 1–3% of the world’s population. Genetic factors play a key role causing the congenital limitations in intellectual functioning and adaptive behavior. The heterogeneity of ID makes it more challenging for genetic and clinical diagnosis, but the advent of large-scale genome sequencing projects in a trio approach has proven very effective. However, many variants are still difficult to interpret. A combined approach of next-generation sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 71 publications
(8 reference statements)
2
53
0
3
Order By: Relevance
“…Several publications allowed its identification as a primary gene for Intellectual Disability (ID), which is the most common developmental disorder affecting 1–3% of the world’s population. Most IDs are monogenic with 1,396 genes causing ID [ 138 ]. The TRIP12 gene is referenced as a causative gene associated with Clark–Baraitser syndrome (CLABARS; OMIM617752), formerly autosomal-dominant mental retardation-49 (MRD49) in the OMIM database.…”
Section: Trip12 In Pathologiesmentioning
confidence: 99%
“…Several publications allowed its identification as a primary gene for Intellectual Disability (ID), which is the most common developmental disorder affecting 1–3% of the world’s population. Most IDs are monogenic with 1,396 genes causing ID [ 138 ]. The TRIP12 gene is referenced as a causative gene associated with Clark–Baraitser syndrome (CLABARS; OMIM617752), formerly autosomal-dominant mental retardation-49 (MRD49) in the OMIM database.…”
Section: Trip12 In Pathologiesmentioning
confidence: 99%
“…It is classified as mild, moderate, severe, or profound based on IQ score. ID is defined as non-syndromic if the intellectual deficit is the sole clinical feature, or as syndromic if the mental impairment is comorbid with other neurologic pathologies such as epilepsy, sensory alterations and ASD (Ilyas et al, 2020). ID is a complex multifactorial disease, in which environmental and genetic factors and their reciprocal interaction critically contribute to its etiology.…”
Section: Id and Impairment Of Ubiquitination And Sumoylation Pathwaysmentioning
confidence: 99%
“…To date, ;700 genes were associated to either syndromic or non-syndromic ID. Notably, more than 50% of these genes encode presynaptic or postsynaptic proteins, or proteins implicated in synapse development, function and plasticity (Ilyas et al, 2020). Among the several genes associated with ID, ;100 genes are located on chromosome (chr.)…”
Section: Id and Impairment Of Ubiquitination And Sumoylation Pathwaysmentioning
confidence: 99%
“…Intellectual disability not only causes a heavy burden on patients and families, but also brings a series of problems in public health, society and education. At present, studies have shown that there are around 1396 genes related to ID [6], and bromodomain and PHD finger-containing protein 1 (BRPF1) is one of them. In the last few years, a total of 40 clinical cases of mental retardation caused by de novo or inherited BRPF1 mutations have been reported [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%